Associations between circulating cardiovascular disease risk factors and cognitive performance in cognitively healthy older adults from the NuAge study - Koblinsky, Noah D.; Carmichael, Pierre-Hugues; Belleville, Sylvie; Fiocco, Alexandra J.; Gaudreau, Pierrette; Greenwood, Carol E.; Kergoat, Marie-Jeanne; Morais, José A.; Presse, Nancy; Laurin, Danielle; Ferland, Guylaine (Frontiers in Aging Neuroscience, 2023)
Highlights 1) HDL-C was shown to be the most robust positive associations with cognition 2) Associations between CVRFs and cognition were observed primarily in females 3) Most CVRFs were not negatively associated with cognition in healthy older adults Abstract (words = 166) Cardiovascular disease risk factors (CVRFs) contribute to the development of cognitive impairment and dementia. This study examined the associations between circulating CVRF biomarkers and cognition in 386 cognitively healthy older adults (mean age = 78 ± 4 years, 53% females) selected from the Quebec Longitudinal Study on Nutrition and Successful Aging (NuAge). Memory, executive function, and processing speed were assessed at baseline and 2year follow-up. CVRF biomarkers included total cholesterol, high-density lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), triglycerides, glucose, insulin, high sensitivity C-reactive protein (hs-CRP), homocysteine, protein carbonyls, and cortisol. Linear mixed models were used to determine associations between individual CVRF biomarkers and cognition at both time points. HDL-C was most consistently associated with cognition with higher values related to better performance across several domains. Overall, stronger and more consistent relationships between CVRF biomarkers and cognition were observed in females relative to males. Findings suggest that increases in the majority of circulating CVRFs are not associated with worse cognition in cognitively healthy older adults.